2021
DOI: 10.1080/02670844.2021.1963626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructural evolution on mechanical and electrical properties of Ag–Mo thin films

Abstract: Herein, Ag-Mo films were deposited on Si(100) substrates by magnetron co-sputtering. The phase evolution and microstructural investigation revealed that the pure Ag phase and no Ag(Mo) solid solution were formed in the Ag-rich films even though the Mo content reached 53 at.%. However, the metastable Mo(Ag) solid solution was formed on the Mo-rich side. The Young's modulus, hardness, resistivity and the relationship between these properties and the microstructural evolution of Ag-Mo films were studied. Precisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…[50][51][52] Additional samples were strained to 15% (pre-tests), where the average saturation crack density was measured via the line intercept method and added to Table 1 to allow for quantitative comparison to other studies. Literature values of Gao et al [30] are shown in Table 1 to allow comparison between similar compositions with the presented work.…”
Section: Electro-mechanical Characterizationmentioning
confidence: 89%
See 3 more Smart Citations
“…[50][51][52] Additional samples were strained to 15% (pre-tests), where the average saturation crack density was measured via the line intercept method and added to Table 1 to allow for quantitative comparison to other studies. Literature values of Gao et al [30] are shown in Table 1 to allow comparison between similar compositions with the presented work.…”
Section: Electro-mechanical Characterizationmentioning
confidence: 89%
“…Saturation crack density at 15% strain was determined from pre-tests. Data combined with literature data for similar compositions extracted from Gao et al [30] using WebPlotDigitizer. [53] Resistivity [Ω m] × 10 accelerating the healing process.…”
Section: Electro-mechanical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The weak diffraction peak of Ag (111) (PDF#04-0783) suggests a duplex-phase microstructure. The location of diffraction peaks in TPs remains unshifted along with increasing Ag content, suggesting that the Ag was not further embedded in the FeCoCr lattice [18]. With further increase in Ag content, the intensity of the Ag (111) peak becomes stronger than that of the FeCoCr phase, suggesting increasing formation of Ag phase.…”
Section: Materials Library and Compositional Gradientmentioning
confidence: 99%